The Relationship Between Age And Sleep Quality Traffic Accidents On Online Motorbike Taxi Drivers In Medan City Year 2024 - Novita Marcelina, Diah; Siregar, Santy Deasy; Hulu, Victor Trismanjaya (PROMOTOR, 2025)
The city of Medan is the capital of the province of North Sumatra, Indonesia, and is the third largest city in the country after Jakarta and Surabaya, as well as the largest outside Java. Medan faces serious problems related to traffic accidents. This study used a questionnaire to explore the relationship between age and sleep quality and the incidence of accidents in online motorcycle taxi drivers. This type of research is quantitative with a cross-sectional design, involving a sample of active online motorcycle taxi drivers from Gojek and Grab partners. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Driver behavior is measured using the Motorcycle Rider Behavior Questionnaire (MBRQ). To increase the accuracy of the analysis of accident factors, researchers also checked the blood pressure of online motorcycle taxi drivers at 08.00 WIB. The results showed that 24 people (66.7%) aged ≥ 35 years were at risk of having an accident, while 24 people (66.7%) experienced problems with drowsiness when driving, 29 people (80.6%) with unsafe behavior when driving so they were at risk. had a traffic accident and 13 drivers showed abnormal blood pressure. To reduce this risk, it is recommended that drivers slow down vehicle speed, get enough sleep, reduce coffee consumption, and obey traffic signs.